AN ANALYSIS OF SUBJECT-VERB AGREEMENT ERRORS ON STUDENTS’ WRITING - Siti Nurjanah (ELT Echo : The Journal of English Language Teaching in Foreign Language Context, 2017)
Abstract: This study is aimed to examine the written subject and verb agreement errors made by the students of management department studying in Universitas Muhammadiyah Yogyakarta when they were writing their paragraphs in present tense. Error analysis technique was carried out in this research in order to find the errors faced by the students in terms of present tense, identify the types of errors as well as the sources of the errors. The research is a descriptive study with 11 students participating in the study. The data of the research were collected from 1) the students’ writings focusing on students’ sentences containing subject-verb agreement errors, and 2) interview to triangulate the data obtained from students’ writings. The findings of the research are as follow: 1) Students’ subject and verb agreements’ errors viewed surface taxonomy’s perspective are in the form of misformation, omission, and addition, while viewed from linguistic categorization’s perspective, the errors are in the form of improper use of singular/plural nouns placed as the subject, inappropriate use of verbs, and improper use of verbal and nominal sentences in making present tense. The analyzed data also show that students’ errors of subject-verb agreement are classified as local errors. 2) The sources of the errors are inter-lingual transfer, intra-lingual transfer, and misleading context of learning.  The research reveals that the students are still having difficulties in using correct patterns of subject and verb agreement in their writing using present tense.  Keywords: Subject and Verb agreement, error analysis, inter-lingual transfer                                intra-lingual transfer